Implementasi Program Bantuan Pangan Non Tunai (BPNT) - Ayu Rosita; Sholih Sholih; Herlina Siregar (Jambura Journal of Community Empowerment, 2024)
The Non-Cash Food Assistance Program (BPNT) is a program implemented by the government in non-cash form given to Beneficiary Families (KPM) with the aim of helping to reduce KPM expenses. This research aims to find out how the Non-Cash Food Assistance (BPNT) program is implemented in Batubantar Village using descriptive research methods and a qualitative approach. The data collection techniques used in this research are observation, interviews and documentation. The results of the research show that the implementation of the Non-Cash Food Assistance (BPNT) program in Batubantar Village has gone well, although the distribution process is still not on target. Keywords: Non-Cash Food Assistance, Implementation